2023
DOI: 10.3390/buildings13081998
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Concrete Carbonation and Approaches to Its Research under Irradiation

Abstract: The current state of knowledge on concrete carbonation has proven that this phenomenon is one of the key factors influencing the reinforced concrete durability reduction during the operational period. To date, the carbonation process has been researched quite deeply; however, the dependence of its course on a variety of external and internal factors poses a significant problem in service life predictions for concrete constructions. The development of nuclear infrastructure around the world in recent years has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Carbonation can significantly lower the pH value of concrete near the steel bars, leading to corrosion, structural damage, and a shorter lifespan for the structure [4,5]. After extensive research, it has been found that the service life of reinforced concrete will significantly decrease after 20-30 years of use due to the influence of carbonation [6]. If left unchecked, the carbonation process can lead to the expansion and cracking of concrete, posing a serious risk to personal safety and property integrity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonation can significantly lower the pH value of concrete near the steel bars, leading to corrosion, structural damage, and a shorter lifespan for the structure [4,5]. After extensive research, it has been found that the service life of reinforced concrete will significantly decrease after 20-30 years of use due to the influence of carbonation [6]. If left unchecked, the carbonation process can lead to the expansion and cracking of concrete, posing a serious risk to personal safety and property integrity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to IAEA documents [1,2], one of the priority research areas in the field of used nuclear fuel storage facilities construction is research into the reinforced concrete structure degradation effects and mechanisms in order to ensure their safe operation [3][4][5][6]. Understanding the mechanisms of concrete degradation in relation to such buildings is inextricably connected to the research into the operating conditions of these structures and external influences leading to accelerated aging of concrete and reinforcing steel [1].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from the table above, the impact of stressors leading to concrete degradation is usually associated with a combination of various internal and external influences. Therefore, it should be taken into account at the design stage of deep-burial storage facilities in order to ensure the resistance of concrete structures to intensive degradation during the design life of the building [1,2,4,[6][7][8]. The cumulative influence of factors leading to con-also occur in deeper layers in the presence of cracks or as a result of prolonged interaction with an aggressive environment [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations